Unearthing Social Issues Due to Rapid Development of Iskandar Malaysia Region Using Exploratory Interview - Ismail, Mohd Firdaus; Yusoff, Wan Zahari Wan; Rahman, Ismail Abdul; Saim, Nur Amylia Izrin Mohd (Tropical Scientific Journal, 2022)
Objective: This paper presents in-depth interviews that was conducted to uncover the social issues faced by residents due to the rapid development of the Iskandar Malaysia economic region. Research Method: Five social experts in the region were involved in the exploratory in-depth interview sessions. The interviewees were free to express their opinions based on open-ended questions with a minimal guide to ensure that their opinions are within the main theme of this study. The interviews were recorded and transcripted, which then, the pertinent points were extracted using thematic analysis. Findings: The analysis of the transcripts uncovered 36 social issues that have been highlighted by the Iskandar Malaysia social experts. Based on the interview, the most emphasised issues were on employment and housing.. Originality: Thematic analysis on social issues present in Iskandar Malaysia as described by experts.